High-performance buildings simplified : designing, constructing, and operating sustainable commercial buildings. - Lawrence, Tom, 1957-; Keen, Julia, 1975- (ASHRAE, 2019)
"Textbook accompaniment to ASHRAE GreenGuide provides practical instruction, assessments, and case studies for engineering students"-- Provided by publisher
Keywords: Commercial buildings.; Sustainable buildings.; elektronické knihy; electronic books